Răspunsul tinerilor la inovaţia educaţională - Mitulescu, Sorin (Calitatea Vieții, 2009)
The paper begins with an inventory of educational innovations currently developing in Romania, when the country is making efforts (together with the European partners) to create a knowledge society. The state of lagging behind is being overcome both at the level of the educational system and that of an alternative education. Several new, nontraditional educational paths are reviewed. Facing these educational challenges and offers, our study tried to register the reaction of pupils and students, who are about to outline a personal educational style, depending on acceptance or ignoration of these innovations. The final conclusion is that, at present, only a small part of the Romanian youngsters is ready to take benefit of the educational innovations. Most of them still have a passive and conservatory mood.